Intention of use of e-health site by PUSKESMAS patients (study in Surabaya City) / Irvan Kurniawan ... [et al.] - Kurniawan, Irvan; Fatiha, Arfiedna Tiara; Mardiyanta, Antun (2021)
The continuous development of ICT has driven drastic changes in people's lives. These changes occur because of the constant emergence of new products and services, new ways of doing businesses, new markets and new investment opportunities, new channels of social and cultural expression, and new channels for interaction between citizens and government (Organization for Economic Cooperation and Development [OECD], 2003:12; Dwivedi & Irani, 2009:125). The development of ICT in public services or the so-called e-Government can facilitate better interaction between citizens and the officials. In other words, e-government attempts to simplify the service process and accommodate citizens' needs. In addition, large amounts of funds have been spent around the world on initiatives to implement egovernment.